+0  
 
0
289
4
avatar

5g+6w-g-6w

 

= 4g+0 

 

am i right??

 Mar 17, 2019
 #1
avatar+6196 
+1

yes or just 4g

 Mar 17, 2019
 #2
avatar+142 
+3

\(5g+6w-g-6w \) 

We can switch \(g\) and \(6w\)

\(5g-g+6w-6w\)

Compute

\(5g-g=4g\) and \(6w-6w=0\)

So \(4g+0\) 

Or just \(4g\)

 

Yes you are right

-KeyLimePi coolcoolcool

 Mar 17, 2019
 #3
avatar
+1

Yes Just first calculate the variables. (5g-g)+(6w-6w)=(5-1)g=4g

 Mar 18, 2019
 #4
avatar+142 
+2

Its a bit basic

 Mar 24, 2019

60 Online Users

avatar
avatar
avatar
avatar